Find f(g(x)) f(x)=2x^2-x g(x)=x^-2

Math
Set up the composite result function.
Evaluate by substituting in the value of into .
Simplify each term.
Tap for more steps…
Multiply the exponents in .
Tap for more steps…
Apply the power rule and multiply exponents, .
Multiply by .
Rewrite the expression using the negative exponent rule .
Combine and .
Rewrite the expression using the negative exponent rule .
Find f(g(x)) f(x)=2x^2-x g(x)=x^-2

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top